Participatory Action Research Untuk Mengurangi Keluhan Efek Neurologis dan Penyakit Hipertensi Pada Lansia di Kampung KB Dusun Kampung Godang, Kabupaten Kampar - Ulfah, Ulfah; Sari, Dita Kartika; Kurniawan, Rahmad; Balqis, Salsabila Putri; Ihsan, Annisa Azzahra (Unri Conference Series: Community Engagement, 2024)
Research-based community service was conducted on the elderly of Dusun Kampung Godang, Pulau Lawas Village, Kampar Regency, which has a Quality Family Village (KB Village) community. The elderly have many complaints of diseases, especially hypertension. The elderly have limited knowledge of preventing neurological effects and hypertension. This paper aims to improve the quality of health of the elderly in the KB Village, focusing on avoiding neurological effects or complaints and hypertension. This elderly community is mostly women and totals 128 people. This study took a sample of 34 respondents with a maximum age of 80. The Participatory Action Research (PAR) method was carried out in a participatory manner among community respondents in a community whose enthusiasm is to encourage transformative actions to solve problems. A series of 2 activities with a time interval of 15 days showed a decrease in hypertension in the elderly. The elderly in the KB Village received efforts to prevent neurological effects through the Participatory Action Research method. Hypertension prevention strategies in KB villages can involve stakeholders in formulating educational activities to reduce the risk of hypertension for the elderly.